Enhanced mucosal response in sheep harbouring βA beta-globin against haemonchosis - Okino, Cintia Hiromi; Niciura, Simone Cristina Méo; Giaretta, Paula Roberta; Melito, Gláucia Roberta; Kapritchkoff, Rafaela Tami Ikeda [UNESP]; Santos, Isabella Barbosa dos [UNESP]; Rech, Raquel Rubia; Minho, Alessandro Pelegrine; Esteves, Sérgio Novita; Chagas, Ana Carolina de Souza (Wiley, 2023)
Association between ovine β-globin polymorphisms and resistance against haemonchosis was described and related to the mechanism of high oxygen affinity βA ➔ βC switch during anaemia, but there are no studies regarding the involved local host responses. Phenotypic parameters and local responses were evaluated in sheep from two β-globin haplotypes naturally infected with Haemonchus contortus. Morada Nova lambs were monitored at 63, 84 and 105 days of age for faecal egg counts and packed cell volume (PCV) under natural infection with H. contortus. At 210 days of age, lambs of Hb-AA and Hb-BB β-globin haplotypes were euthanised, and the fundic region of abomasum was sampled for evaluation of microscopic lesions and relative expression of genes related to immune, mucin and lectin activities. Lambs harbouring the βA allele presented an improved resistance/resilience against clinical haemonchosis, showing higher PCV during infection. Hb-AA animals presented increased eosinophilia in the abomasum compared to Hb-BB animals, accompanied by higher Th2 profile, mucin and lectin activity transcripts, while the inflammatory response was increased in Hb-BB animals. This is the first report to demonstrate an enhanced local response in the primary site of H. contortus infection related to βA allele of β-globin haplotype.
Keywords: abomasum; Haemonchus contortus; haplotype; lectins; mucin; ovine; RT-qPCR